Open Innovation Strategy in Goods Manufacturing and Service Industries - Raden Roro Shafira Meisy Sudarsono; Harimukti Wandebori; Anggun Siwi Murwati; Atik Aprianingsih (International Journal of Entrepreneurship and Sustainability Studies, 2022)
Globalization and digitalization have increased the necessity for open innovation (OI) as a strategy for businesses to understand customers' needs better. The OI paradigm has gathered importance in academic research and industrial applications. Simultaneously, both goods manufacturing and service industries have been invested in OI in order to improve productivity and meet market demands. Considering this interest, this paper aims to synthetize findings, outline the focus application of OI within the goods manufacturing and service goods research domain, and suggest a future research agenda. Our analysis reveals that in the literature, OI in the manufacturing sector have tendencies of adopting both inbound and outbound OI in their practices. Meanwhile, service industries are inclined to adopt inbound OI than outbound OI.